Origins and impact of constraints in evolution of gene families - Shakhnovich, Boris E.; Koonin, Eugene V. (Genome Research, 2006)
Recent investigations of high-throughput genomic and phenomic data have uncovered a variety of significant but relatively weak correlations between a gene’s functional and evolutionary characteristics. In particular, essential genes and genes with paralogs have a slight propensity to evolve more slowly than nonessential genes and singletons, respectively. However, given the weakness and multiplicity of these associations, their biological relevance remains uncertain. Here, we show that existence of an essential paralog can be used as a specific and strong gauge of selection. We partition gene families in several genomes into two classes: those that include at least one essential gene (E-families) and those without essential genes (N-families). We find that weaker purifying selection causes N-families to evolve in a more dynamic regime with higher rates both of duplicate fixation and pseudogenization. Because genes in E-families are subject to significantly stronger purifying selection than those in N-families, they survive longer and exhibit greater sequence divergence. Longer average survival time also allows for divergence of upstream regulatory regions, resulting in change of transcriptional context among paralogs in E-families. These findings are compatible with differential division of ancestral functions (subfunctionalization) or emergence of novel functions (neofunctionalization) being the prevalent modes of evolution of paralogs in E-families as opposed to pseudogenization (nonfunctionalization), which is the typical fate of paralogs in N-families. Unlike other characteristics of genes, such as essentiality, existence of paralogs, or expression level, membership in an E-family or an N-family strongly correlates with the level of selection and appears to be a major determinant of a gene’s evolutionary fate.